Protonation linked equilibria and apparent affinity constants: the thermodynamic profile of the alpha-chymotrypsin-proflavin interaction. - Bruylants, G; Wintjens, R; Looze, Y; Redfield, C; Bartik, K (2007)
Protonation/deprotonation equilibria are frequently linked to binding processes involving proteins. The presence of these thermodynamically linked equilibria affects the observable thermodynamic parameters of the interaction (K(obs), DeltaH(obs)(0) ). In order to try and elucidate the energetic factors that govern these binding processes, a complete thermodynamic characterisation of each intrinsic equilibrium linked to the complexation event is needed and should furthermore be correlated to structural information. We present here a detailed study, using NMR and ITC, of the interaction between alpha-chymotrypsin and one of its competitive inhibitors, proflavin. By performing proflavin titrations of the enzyme, at different pH values, we were able to highlight by NMR the effect of the complexation of the inhibitor on the ionisable residues of the catalytic triad of the enzyme. Using ITC we determined the intrinsic thermodynamic parameters of the different equilibria linked to the binding process. The possible driving forces of the interaction between alpha-chymotrypsin and proflavin are discussed in the light of the experimental data and on the basis of a model of the complex. This study emphasises the complementarities between ITC and NMR for the study of binding processes involving protonation/deprotonation equilibria.